Caffeine Use and Attentional Engagement in Everyday Life - Tyler B. Kruger; Mike J. Dixon; Daniel Smilek (Current Research in Behavioral Sciences)
Caffeine is a common component of various beverages and foods with approximately 80% of the world's population consuming caffeinated products daily. Here we examined how caffeine consumption and different motivations for consuming caffeine (e.g., cognitive enhancement, negative affect relief, reinforcing effects, and weight control) relate to self-reported inattention, mind-wandering, and deep, effortless concentration (i.e., flow) in everyday life in a university student population via two online surveys (N = 224 and N = 234). Our results indicated that, contrary to what one might expect, the amount of caffeine consumed in a typical day (estimated in milligrams) was not related to attention-related experiences in everyday life. However, we found that those who are more likely to ingest caffeine to potentially enhance their cognition, or to experience the reinforcing effects of caffeine, or to help relieve negative affect showed higher levels of inattention in everyday life.